Associations between red cell distribution width and in-hospital mortality in congestive heart failure patients with chronic obstructive pulmonary disease: a retrospective cohort study - Li, Mixia; Zhang, Kai; Shi, Yu; Cai, Tianyi; Gu, Zhao Xuan; Han, Yu; Gu, Fang Ming; Zhang, Tian Qi; Gao, Min; Li, Bo; Cui, Dan; Liu, Kexiang (Frontiers in Medicine, 2025)
BackgroundRecent studies have identified a co-occurrence of chronic obstructive pulmonary disease and congestive heart failure in ICU patients. Abnormal red cell distribution width (RDW) frequently manifests in critically ill patients, but its clinical significance remains a subject of debate. This study aims to investigate the relationship between RDW and in-hospital mortality in patients with concurrent congestive heart failure and chronic obstructive pulmonary disease.MethodsWe conducted a retrospective cohort study using the Medical Information Mart for Intensive Care (MIMIC) IV version 2.0 database. RDW levels were assessed within 24 h of admission. The impact of RDW at ICU admission on in-hospital mortality was analyzed through multivariable logistic regression models, generalized additive models, and subgroup analysis.ResultsWe enrolled 6,309 patients with congestive heart failure and concomitant chronic obstructive pulmonary disease, with an in-hospital mortality rate of 12.4% (783/6,309). The fully adjusted model revealed a positive association between RDW and in-hospital mortality in congestive heart failure patients with concurrent chronic obstructive pulmonary disease, even after accounting for confounding factors (OR = 1.07, 95% CI: 1.03–1.12, p < 0.001). When comparing the highest quartile (Q4) to the lowest quartile (Q1), the odds ratio (OR) was 1.62, with a 95% confidence interval (CI) of 1.17–2.22, p = 0.003. We observed a linear relationship between RDW and in-hospital mortality, which remained consistent in subgroup analysis.ConclusionsOur data suggest that RDW is positively associated with in-hospital mortality in patients with both congestive heart failure and chronic obstructive pulmonary disease. At the same time, large prospective research and longer follow-up time are required to further validate the findings of this study.